Double Trouble: Chronic Cavitary Pulmonary Aspergillosis with Endobronchial Chondroma, Arising Post-Tuberculosis - Kulkarni, Saumitra; Yadav, Kritika Singh; Bhalekar, Surekha (Annals of Pathology and Laboratory Medicine, 2025)
Pulmonary tuberculosis is a common infectious condition mainly seen in developing countries like India. It is particularly important because of its long-term complications such as chronic cavitary pulmonary aspergillosis. Endobronchial chondroma is an extremely rare benign tumor which presents with nonspecific respiratory symptoms. We report a case of a previously treated tuberculosis patient in whom both chronic cavitary aspergillosis and endobronchial chondroma were diagnosed concurrently on final histopathological examination of the surgical specimen.